2018
DOI: 10.1111/liv.13931
|View full text |Cite
|
Sign up to set email alerts
|

The diagnosis and management of idiosyncratic drug‐induced liver injury

Abstract: Drug-induced liver injury (DILI) is an uncommon but important cause of liver disease that can arise after exposure to a multitude of drugs and herbal and dietary supplements. The severity of idiosyncratic DILI varies from mild serum aminotransferase elevations to the development of severe liver injury that can progress to acute liver failure resulting in death or liver transplantation within days of DILI onset. Chronic liver injury that persists for more than 6 months after DILI onset is also becoming increasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 93 publications
0
39
0
Order By: Relevance
“…Responses to comments on the original version of RUCAM of 1993 (Hassan and Fontana, 2019) were provided and already implemented in the updated version (Danan and Teschke, 2016). Other comments were addressed in a summary table (Danan and Teschke, 2018) and in detailed work instructions (Electronic supplementary material in Danan and Teschke, 2018).…”
Section: Future Use Of Rucammentioning
confidence: 99%
“…Responses to comments on the original version of RUCAM of 1993 (Hassan and Fontana, 2019) were provided and already implemented in the updated version (Danan and Teschke, 2016). Other comments were addressed in a summary table (Danan and Teschke, 2018) and in detailed work instructions (Electronic supplementary material in Danan and Teschke, 2018).…”
Section: Future Use Of Rucammentioning
confidence: 99%
“…Patients with acute hepatitis and elevated prothrombin time or international normalized ratio levels without mental status changes are frequently labeled as having a severe acute liver injury[25].…”
Section: Definitionsmentioning
confidence: 99%
“…We followed the definition of chronic DILI of the American College of Gastroenterology Clinical Guideline, if LFTs did not return to normal within 6 months after drug withdrawal, regardless of the types of liver injury. Based on the definition of chronic DILI, the incidence of chronic DILI was up to 23.6%, which was higher than the known incidence in the other registrations . The latest research of DILIN workshop showed an incidence of 17% of chronic DILI .…”
Section: Discussionmentioning
confidence: 80%